OPTIMALISASI PEMBERIAN PUTIH TELUR AYAM RAS UNTUK MENINGKATKAN KEMEKARAN KERUPUK IKAN BELUT - Candra Candra; Rabiatul Adawyah (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2012)
This study aims to find the optimal concentration of egg whites to increase efflorescence swamp eel crackers with treatment A without giving egg white, egg white treatment B adding 25 ml, treatment C the addition of 50 ml of egg white and egg white treatment D adding 75 ml. All treatments are performed replications with three replications completely randomized design. Parameters measured were protein content, moisture content, carbohydrate content, crispness test, efflorescence and sensory test. Based on the results of this study concluded giving egg whites to increase the protein content and efflorescence and crispy swamp eel crackers and meet industry standards of Indonesia.